One Hundred Years of Chemical Warfare: Research, Deployment, Consequences - Friedrich, Bretislav; Hoffmann, Dieter; Renn, Jürgen; Schmaltz, Florian; Wolf, Martin (Springer Nature, 2017)
Fritz Haber; Military-Industrial Complex; 1925 Geneva Protocol; Ethics of Chemical Warfare; Dual-use Problem; Anti-plant Chemical Warfare; Chemical Weapons During World War I; Chemical Weapons During World War II; Chemical Weapons in the Middle East; Weapons of Mass Destruction; Lethal Unitary Chemical Agents and Munitions